Drivers and Obstacles of Open Access Publishing. A Qualitative Investigation of Individual and Institutional Factors - Greussing, Esther; Kuballa, Stefanie; Taddicken, Monika; Schulze, Mareike; Mielke, Corinna; Haux, Reinhold (Frontiers in Communication, 2020)
Open Access (OA) is an evolving publication model that is heavily supported by politics and science organizations aiming to make scientific knowledge more accessible to a wider audience. Whether it will indeed alter scholarly communication, however, depends on researchers’ underlying attitudes, motivations and needs. Drawing on group discussions and interviews (n = 42), this study explores the perceptions, attitudes and behaviours of researchers towards OA publishing. We focus on researchers in the field of biomedical and health informatics located in different global regions and from different seniority levels. Overall, the results show that whilst most researchers support the idea of making scientific knowledge freely accessible to everyone, they are hesitant about actually living this practice by choosing OA journals to publish their own work. Article processing charges and quality issues are perceived as the main obstacles in this respect, revealing a two-sided evaluation of OA models, reflecting the different viewpoints of researchers as authors or readers. The results further highlight hitherto underexplored influencing factors regarding institutional frame conditions, located on the level of the scientific system, the publication service providers or the national/international OA policies.